Reconstitution de la vie à bord d’un navire de la Compagnie des Indes orientales au xviiie siècle - Jean-Baptiste Barreau; Ronan Gaugne; Anne-Hélène Olivier; Sylviane Llinares; Valérie Gouranton (In Situ)
Historical reconstructions based on new technologies such as virtual reality are now being developed. However, most of these reconstructions offer frozen worlds, emptied of human activity. As part of a collaboration between a research centre in history, a research institute in computer science and the 3D production platform CNPAO “Digital Conservatory of Western Archaeological Heritage”, we offer a reconstruction of activities of life aboard the ship of the French East India Company, Le Boullongne, based on motion captureA first work made in 2014 produced a functional and interactive simulation of the Boullongne, with virtual reality. This reconstruction already included some animated virtual sailors and animals, but without significant any activity. In this new work, about ten scenes of everyday life have been identified through the study of historical documents and engravings. These scenes were scripted and played by historians involved in the project, and captured and processed by computer scientists. Digital mariners have been modelled by the CNPAO, in collaboration with historians. In the end, several scenes were integrated in the virtual Boullongne thus giving to the reconstitution a human dimension for this testimony of the life of the sailors aboard the ships of the 18th century.